2020
DOI: 10.17522/balikesirnef.782321
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Geometriye Yönelik İnanç ve Tutumlarının Başarıları ile Olan İlişkisi

Abstract: In this study, it is aimed to investigate the relationship between the beliefs and attitudes of the secondary school students towards geometry and their mathematical achievements. The extent to which the belief and attitude towards geometry predicts mathematics achievement is another subject. The study was designed with a quantitative method, survey method. Research, located on Turkey's Mediterranean Coast from secondary schools in the province chosen by simple random sampling medium sized secondary school in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…When the attitudes towards geometry were examined by gender, no significant difference was observed in the attitude scores of female and male students towards geometry. While Sevgi and Gürtaş (2020) and Yücel and Koç (2011), who worked with of middle school students, also found no significant difference in attitudes according to the gender; İlhan, Gemcioğlu and Poçan (2021) and Kaba, Daymaz and Boğazlıyan (2016) found significant differences by gender. Kaba et al (2016) found that female students' attitudes towards mathematics were more positive compared to male students' attitudes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…When the attitudes towards geometry were examined by gender, no significant difference was observed in the attitude scores of female and male students towards geometry. While Sevgi and Gürtaş (2020) and Yücel and Koç (2011), who worked with of middle school students, also found no significant difference in attitudes according to the gender; İlhan, Gemcioğlu and Poçan (2021) and Kaba, Daymaz and Boğazlıyan (2016) found significant differences by gender. Kaba et al (2016) found that female students' attitudes towards mathematics were more positive compared to male students' attitudes.…”
Section: Discussionmentioning
confidence: 91%
“…There are studies examining the effect of material use on attitude in the framework of the research on attitudes towards geometry (Yemen, 2009;Budak, 2010;Önal and Demir, 2012;Şeker, 2014;Orçanlı, 2015;Sarıaslan and Küçük Demir, 2019;Topraklıoğlu, 2019;Özmen, 2019 ;Göksu, 2020;Frazier, 2020) and studies on determining the attitude towards geometry and whether it differed in terms of demographic characteristics (Bulut et al, 2002;Bindak, 2004;Aktaş and Aktaş, 2012;Mahanta, 2012;Hızlı, 2013;Sunzuma, Masocha and Zezekwa, 2013;Avcı et al, 2014;Melo and Martins, 2015;Kaba Daymaz and Boğazlıyan, 2016;Bora and Ahmed, 2018;Özdişçi, 2019;Ylano and Tayaben, 2019;Auliya and Munasiah, 2020;Bulut et al, 2020;Sevgi and Gürtaş, 2020;İlhan, Gemcioğlu and Poçan, 2021;Yücel and Koç, 2021) while studies on perceived school experiences usually centered on metaphor studies on school life Özdemir and Yüner, 2017;Arslan, 2020), on factors such as academic motivation and commitment to school (Finn, 1993;Arastam, 2009;Middleton and Midgley, 2002;Bozanoglu, 2004;Dogan, 2014;Fan and Williams, 2018) and on perceived school experiences in terms of demographic characteristics (Güler, 2019). Based on the relevant literature review, no research was found on the relationship between middle school students' attitudes towards geometry and their perceived school experiences.…”
Section: Introductionmentioning
confidence: 99%